(untitled) (Italian Journal of Public Health, 2008)
Background: People start smoking during childhood and adolescence and the age at which children start smoking is gradually falling: in 2005, it rose to 3.3% in the 11-to-14 year age group whereas in 2002 it was only 1.4% in the same age group. Methods: “Mr Starbene e il Club dei Vincenti”, part of a regional program, Liberi dal Fumo, was assessed through an experimental non-randomized study, by involving parents and teachers, using short questionnaires. The project’s objective was orienting fourth and fifth grade children towards a no-smoking lifestyle. The enrolled population was composed of 5,552 students in the treatment group and 4,758 controls. Results:: after two years, the number of children who had tried smoking but no longer smoked at the moment decreased by 16.3% in the treatment group, while it increased by 12.5% in the controls (p=0.000). The number of children who considered smoking a few cigarettes/day dangerous was higher in the treatment group (+8%) than in the controls (+4.4%) which suggests significant results vis-à-vis perceived smoking hazards. Children who claimed they would not smoke in the future decreased by 57.1% in the treated group as compared with a 21.4% reduction in the control group (p<0.001); children who said they would accept an offer of a cigarette decreased in the treated group (-12.5%), but not in the controls (p<0.001). The study pointed out also the influence of role-models in children attitudes toward smoking. Conclusions: The positive results of this project give rise to hope for the future, even if long term evaluation is necessary. The good scores obtained from the teachers are very positive because they make the project work.